2005
DOI: 10.1111/j.0197-3118.2005.04324.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Endurance Exercise Training and VO2max Changes in Older Adults: A Meta‐Analysis

Abstract: This meta-analysis of controlled clinical trials quantifies the effect of aerobic exercise on VO2max (aerobic fitness) among sedentary older adults and examines the associations of such magnitude with variables of intervention. Forty-one trials including 2102 older subjects (within-group mean age of 60 years and older) were identified by searches of databases, hand searching, and cross-referencing. Outcomes were homogeneous. The pooled standardized effect size by a fixed-effect model showed a higher moderate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 50 publications
5
55
0
1
Order By: Relevance
“…This preconditioning exercise proved effective in that all SED participants who completed training block 1 also completed the HIIT intervention. The magnitude of improvement in aerobic fitness following preconditioning is in line with previous similar exercise interventions involving previously sedentary participants (Gormley et al 2008;Huang et al 2005). As expected,VO 2max in the LEX group both prior to and following training block 1 was within the standard error of measurement.…”
Section: Discussionsupporting
confidence: 88%
“…This preconditioning exercise proved effective in that all SED participants who completed training block 1 also completed the HIIT intervention. The magnitude of improvement in aerobic fitness following preconditioning is in line with previous similar exercise interventions involving previously sedentary participants (Gormley et al 2008;Huang et al 2005). As expected,VO 2max in the LEX group both prior to and following training block 1 was within the standard error of measurement.…”
Section: Discussionsupporting
confidence: 88%
“…VO 2 max is a widely used measurement of stable aerobic fitness, and can be improved with training depending on exercise intensity and consistency ( e.g. Huang et al, 2005). Participants were asked not to engage in strenuous physical activity for at least 24 hours prior their scheduled fitness test, and not to consume food or caffeine for at least 3 hours prior.…”
Section: Methodsmentioning
confidence: 99%
“…Three small meta-analyses reported significant increases in CRF in response to selected HIT and MICT regimens in patients with various manifestations of CVD. 277,286,287 In another meta-analysis, 6 randomized clinical trials with a total of 153 patients were included, but only 4 randomized controlled trials with 111 patients had adequately reported peak/maximal V ⋅ o 2 data. 277 Compared with MICT, HIT significantly improved peak/maximal V ; 95% confidence interval, 2.3-4.9).…”
Section: High-intensity Training and Crfmentioning
confidence: 99%